Anti-BACE1 and anti-AchE activities of undescribed spiro-dioxolane-containing meroterpenoids from the endophytic fungus Aspergillus terreus Thom. (September 2019) - Qi, Changxing; Zhou, Qun; Gao, Weixi; Liu, Mengting; Chen, Chunmei; Li, Xiao-Nian; Lai, Yongji; Zhou, Yuan; Li, Dongyan; Hu, Zhengxi; Zhu, Hucheng; Zhang, Yonghui
Abstract: Spiroterreusnoids A–F, six undescribed spiro-dioxolane-containing adducts bearing 3, 5-dimethylorsellinic acid-based meroterpenoid and 2, 3-butanediol moieties were isolated from the endophytic fungus Aspergillus terreus Thom from Tripterygium wilfordii Hook. f. (Celastraceae). The structures of these adducts were established by spectroscopy, single-crystal X-ray diffraction, and experimental electronic circular dichroism (ECD) measurements. Spiroterreusnoids A–F represent the first examples of adducts composed of 3, 5-dimethylorsellinic acid-based meroterpenoids. It is noteworthy that spiroterreusnoids A–F possessing a spiro-dioxolane moiety exhibited potential abilities in inhibiting BACE1 (IC50 values ranging from 5.86 to 27.16  μ M) and AchE (IC50 values ranging from 22.18 to 32.51  μ M), while the other analogues without this fragment displayed no such activities. Taken together, spiroterreusnoids A–F represent the first multitargeted natural adducts that could inhibit BACE1 and AchE, and might provide a new template for the development of new anti-Alzheimer's disease drugs. Graphical abstract: Image 1 Highlights: Spiro-dioxolane-containing adducts were isolated from the fungus Aspergillus terreus. Spiroterreusnoids A–F were composed of 3, 5-dimethylorsellinic acid-based meroterpenoid. Spiroterreusnoids A–F exhibited potential abilities in inhibiting BACE1 and AchE. Spiroterreusnoids A–F were the natural adducts that could inhibit BACE1 and AchE.